Tensile testing of polymers: Integration of digital image correlation, infrared thermography and finite element modelling - Song, P; Trivedi, A; Siviour, CR (Elsevier, 2022)
Tensile tests are often used as part of material characterisation strategies; however, the observed deformation is often complex, and it can be difficult to distinguish the underlying material behaviour from the structural response of the specimen. The objective of the research in this paper was to investigate whether a more accurate calibration of a material model could be obtained by considering not just the global behaviour of the specimen, but also the local strain-time response calculated from full-field displacement information obtained using digital image correlation. Tensile experiments were performed using ISO standard, flat, dog bone specimens. Optical and infra-red imaging were used to calculate full field displacement and temperature maps, and a finite element model of the experiment was produced. These were combined with compression test data from the same material to calibrate a constitutive model, which was shown to describe well the deformation and temperature rise in the specimen. The research demonstrates that it is insufficient to use force-displacement information from tensile experiments to calibrate, or validate, constitutive models of polymers. Further, it demonstrates a more applicable method, which could be further automated in the future.